Bacterial community composition in Adélie (Pygoscelis adeliae) and Chinstrap (Pygoscelis antarctica) Penguin stomach contents from Signy Island, South Orkney Islands - Yew, W.C.; Pearce, D.A.; Dunn, M.J.; Samah, A.A.; Convey, P. (Springer Verlag (Germany), 2017)
Penguin stomach microbiota and its variability are important as these microbes may contribute to the fitness of the host birds and their chicks, and influence the microbial ecosystem of the surrounding soils. However, there is relatively little knowledge in this area, with the majority of studies focused on their deposited faeces. Here we investigated whether similar foraging strategies in adjacent colonies of different penguin species lead to similar temporarily conserved stomach microbiota. To do this, we studied the inter- and intra-specific variations in bacterial community composition in the stomach contents of sympatrically breeding Adélie (Pygoscelis adeliae) and Chinstrap (Pygoscelis antarctica) Penguins, which consumed a diet of 100% Antarctic krill (Euphausia superba) under a similar foraging regime on Signy Island (maritime Antarctic), using a high-throughput DNA sequencing approach. Our data show that Adélie and Chinstrap Penguins shared 23–63% similarity in the stomach bacterial community composition, with no significant differences observed in the α-diversity or the assemblages of frequently encountered groups of operational taxonomic units (OTUs). The most frequently encountered OTUs that were shared between the species represented members of the phyla Fusobacteria, Firmicutes, Tenericutes and Proteobacteria. OTUs which were unique to individual birds and to single species formed approximately half of the communities identified, suggesting that stomach microbiota variability can occur in penguins that forage and breed under similar environmental conditions.